1t'-mote2 / ga2o3 schottky gate field effect transistor and preparation method thereof
Patent Information
- Application Number
- CN202410053675.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-01-12
AI Technical Summary
Existing β-Ga2O3 channel layer devices suffer from high turn-on voltage and interface defects, and their performance is unstable in deep cryogenic environments, making it difficult to meet the needs of practical applications. In particular, there is a lack of research on cryogenic operation in outer space environments.
A 1T'-MoTe2/Ga2O3 Schottky gate field-effect transistor structure is adopted. A high-quality van der Waals interface junction is formed by 1T'-MoTe2 nanosheets and β-Ga2O3 nanoribbons, combined with a SiO2/p-Si substrate. The fabrication method includes mechanical exfoliation, electron beam lithography and evaporation processes to form a stable Schottky barrier gate.
It achieves electrical characteristics of low turn-on voltage, low turn-off current, high switching current ratio and steep subthreshold swing. The device performs well at both room temperature and deep cryogenic temperature, and is suitable for space exploration and military applications.
Smart Images

Figure CN117766565B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to semiconductor devices, and more particularly to a 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor and its fabrication method. Background Technology
[0002] In recent years, wide bandgap material β-Ga2O3 has become increasingly popular due to its ultra-large bandgap E. g (4.7-5.3eV), relatively high critical breakdown electric field E c With advantages such as (6-8 MV / cm), good radiation resistance, and thermal stability, β-Ga2O3 substrates have attracted widespread attention from researchers worldwide. High-quality β-Ga2O3 substrates can be used in high-voltage and high-power electronic devices. (Approximately 300 cm⁻¹) 2 V -1 s -1 With its high electron mobility, β-Ga₂O₃ exhibits an extremely high Baliga figure of merit (FOM, 3214.1), far exceeding that of similar semiconductors GaN and SiC. This makes β-Ga₂O₃ a strong candidate for next-generation power electronic devices.
[0003] Currently, researchers have developed various low-cost methods for growing bulk single crystals of Ga2O3, such as the optical floating zone method, the Czochralski method, and the mode-guided method. Furthermore, they have achieved growth rates as low as 10... 16 -10 19 cm -3 The effective carrier concentration of Ga2O3 crystals can be tuned over a wide range. Furthermore, compared to other wide-bandgap materials, another unique property of β-Ga2O3 is that low-dimensional β-Ga2O3 nanoribbons can be obtained using a simple mechanical exfoliation method. Researchers have also fabricated various three-terminal devices based on β-Ga2O3 nanoribbons, such as bottom-gate field-effect transistors (FETs), top-gate FETs, and dual-gate FETs.
[0004] However, the development of β-Ga2O3 channel layer devices is still in its early stages, and many technical challenges remain to be solved. For example, common β-Ga2O3 MOSFETs generally require a high turn-on voltage and suffer from β-Ga2O3 / gate dielectric interface defects, making it difficult to meet practical application requirements. On the other hand, wide-bandgap semiconductor devices, due to their strong radiation resistance, are widely used in the development of artificial satellites and various space missions. β-Ga2O3 is a strong contender, and many reports have investigated the effects of particle irradiation on it (J. Mater. Chem. C, 2019, 7, 10-24). However, in the outer space environment, cryogenic conditions are unavoidable. Currently, research on the cryogenic operating state of β-Ga2O3 three-terminal devices remains lacking. Summary of the Invention
[0005] The purpose of this invention is to provide a 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor and its fabrication method, so as to solve the problems existing in the prior art.
[0006] The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor described in this invention comprises a β-Ga2O3 nanoribbon on a SiO2 / p-Si substrate, with the drain and source electrodes connected to opposite sides of the β-Ga2O3 nanoribbon, respectively; and a 1T'-MoTe2 nanosheet disposed on the upper surface of the β-Ga2O3 nanoribbon, with one end of the 1T'-MoTe2 nanosheet connected to the β-Ga2O3 nanoribbon and the other end connected to the gate electrode.
[0007] One end of the 1T'-MoTe2 nanosheet is connected to the middle of the β-Ga2O3 nanoribbon.
[0008] The SiO2 / p-Si substrate comprises a SiO2 layer and a p-type Si layer stacked sequentially from top to bottom, and the β-Ga2O3 nanoribbon is disposed on the end face of the SiO2 layer away from the p-type Si layer.
[0009] The SiO2 thickness is 100 nm.
[0010] The 1T'-MoTe2 nanosheets are few-layer two-dimensional materials of the 1T' phase.
[0011] The 1T'-MoTe2 nanosheets and β-Ga2O3 nanoribbons extend perpendicularly to the upper surface of the SiO2 / p-Si substrate.
[0012] The preparation method described in this invention is used to prepare a 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor as described above, and includes the following steps:
[0013] S1. Preparation of SiO2 / p-Si substrate;
[0014] S2. Preparation of β-Ga2O3 nanoribbons and electrodes at both ends;
[0015] S3. Prepare 1T'-MoTe2 nanosheets to form a Schottky barrier gate.
[0016] Step S1 specifically involves: growing a 100 nm SiO2 layer on a p-type Si layer using plasma-enhanced chemical vapor deposition; sequentially ultrasonically cleaning the substrate surface for 20 min each with acetone, ethanol, and deionized water to remove organic impurities; and finally drying it with nitrogen gas.
[0017] Step S2 specifically includes the following sub-steps:
[0018] S21. Using 3M tape, mechanically peel off a 140nm thick β-Ga2O3 nanoribbon from the (100) crystal plane of the β-Ga2O3 bulk single crystal and transfer it to the SiO2 / p-Si substrate of step S1.
[0019] S22. Spin coat electron beam photoresist onto the spin coater tray; spin coater speed: forward rotation 500 rad / min, forward rotation time 5s; backward rotation 4000 rad / min, backward rotation time 65s;
[0020] S23. Soften the glue on the drying table. The heating temperature of the drying table is 170℃, and the drying time is 3 minutes and 40 seconds.
[0021] S24. Perform electron beam exposure to symmetrically fabricate drain and source patterns at both ends of the β-Ga2O3 nanoribbon;
[0022] S25. Immerse in developer for 65 seconds, then remove and dry with N2; then immerse in isopropanol solution for 65 seconds, then remove and dry with N2.
[0023] S26. Electron beam evaporation is used to deposit a multilayer metal Ti / Al / Au on the side with the photolithographic pattern, which are used as the source and drain of the device, respectively; the thickness of the multilayer metal is 15 / 90 / 80 nm, and the formation temperature is 50℃;
[0024] S27. Soak in acetone solution, use an ultrasonic cleaner to remove the remaining photoresist until the surface pattern is fully visible, rinse with deionized water and dry with N2.
[0025] S28. Annealing under nitrogen conditions using a rapid thermal annealing apparatus to obtain an ohmic contact electrode; annealing temperature 460℃, annealing time 90s.
[0026] Step S3 specifically includes the following sub-steps:
[0027] S31. Using a blue film, a few-layer 1T'-MoTe2 nanosheet with a thickness of 30 nm was mechanically exfoliated from the 1T' phase MoTe2 bulk crystal and transferred onto a flat PDMS.
[0028] S32. With the assistance of a two-dimensional material transfer platform, the sample obtained in step S31 is aligned and transferred to the middle region of the β-Ga2O3 nanoribbon, and the sample stage heating temperature is 70℃.
[0029] S33. Fix the sample obtained in step S32 onto the spin coater tray and spin coat it with electron beam photoresist. Spin coater speed: forward rotation 500 rad / min, forward rotation time 5s; backward rotation 4000 rad / min, backward rotation time 65s;
[0030] S34. Soft bake on the baking table at a heating temperature of 90℃ for 3 minutes;
[0031] S35. Perform electron beam exposure to create an electrode pattern at one end of the 1T'-MoTe2 nanosheet;
[0032] S36. Immerse in developing solution for 65 seconds, then remove and dry with N2; then immerse in isopropanol for fixing for 65 seconds, then remove and dry with N2.
[0033] S37. A multilayer metal Ti / Au is deposited on the side of the sample with a photolithographic pattern using an electron beam evaporation process to serve as the gate of the device: the thickness of the multilayer metal is 10 / 50 nm, and the formation temperature is 50 °C.
[0034] S38. Immerse in acetone solution and place on a hot plate for heating. The hot plate temperature is 50°C and the heating time is 1 hour. After removing, rinse with deionized water until the surface pattern is fully visible. Blow dry with N2 to obtain the final device.
[0035] The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor and its fabrication method described in this invention have the advantage of using two-dimensional metallic 1T'-MoTe2 nanosheets as the Schottky barrier gate. These nanosheets can form a high-quality van der Waals interface junction with the β-Ga2O3 nanoribbon channel, enhancing the transistor's gate control capability and interface characteristics. This results in a very low turn-on voltage, very low turn-off current, a high on / off current ratio, and a steep subthreshold swing. Even at cryogenic temperatures, the device maintains minimal hysteresis and excellent electrical characteristics. This solves the problem of excessively high turn-on voltage in existing Ga2O3 micro / nano transistors, enabling applications not only at room temperature but also in cryogenic environments, with broad application prospects in space exploration and military fields. Furthermore, the nanosheet / nanoribbon composite structure transistor exhibits high yield and strong repeatability, achieving device miniaturization. Attached Figure Description
[0036] Figure 1 This is a schematic diagram of the structure of a 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor described in this invention.
[0037] Figure 2 This is a schematic diagram of the preparation method described in this invention. Figure 1 .
[0038] Figure 3 This is a schematic diagram of the preparation method described in this invention. Figure 2 .
[0039] Figure 4 This is a schematic diagram of the preparation method described in this invention. Figure 3 .
[0040] Figure 5 This is a schematic diagram of the preparation method described in this invention. Figure 4 .
[0041] Figure 6 yes Figure 5 A top view of the state.
[0042] Figure 7 This is an optical microscope image of 1T'-MoTe2 nanosheets transferred onto PDMS using the preparation method described in this invention; the black background is PDMS, and the bright stripes are the exfoliated MoTe2 nanosheets.
[0043] Figure 8 This is a schematic diagram of the preparation method described in this invention. Figure 5 .
[0044] Figure 9 This is a schematic diagram of the preparation method described in this invention. Figure 6 .
[0045] Figure 10 The graphs show the transfer characteristics of the 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor described in this invention and the comparative example at room temperature.
[0046] Figure 11 This is a graph showing the hysteresis transfer characteristics of the 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor described in this invention at a low temperature of -100℃.
[0047] Figure label:
[0048] p-type Si layer 101, SiO2 layer 102, source 103, drain 104, gate 105; β-Ga2O3 nanoribbon 106, 1T'-MoTe2 nanosheet 107;
[0049] Photoresist layer 201. Detailed Implementation
[0050] like Figure 1 As shown, the 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor of the present invention has a β-Ga2O3 nanoribbon on a SiO2 / p-Si substrate, with the drain and source electrodes connected to opposite sides of the β-Ga2O3 nanoribbon, respectively; and a 1T'-MoTe2 nanosheet is disposed on the upper surface of the β-Ga2O3 nanoribbon, with one end of the 1T'-MoTe2 nanosheet connected to the β-Ga2O3 nanoribbon and the other end connected to the gate electrode.
[0051] One end of the 1T'-MoTe2 nanosheet is connected to the middle of the β-Ga2O3 nanoribbon.
[0052] The SiO2 / p-Si substrate comprises a SiO2 layer and a p-type Si layer stacked sequentially from top to bottom, and the β-Ga2O3 nanoribbon is disposed on the end face of the SiO2 layer away from the p-type Si layer.
[0053] The SiO2 thickness is 100 nm.
[0054] The 1T'-MoTe2 nanosheets are few-layer two-dimensional materials of the 1T' phase.
[0055] The 1T'-MoTe2 nanosheets and β-Ga2O3 nanoribbons extend perpendicularly to the upper surface of the SiO2 / p-Si substrate.
[0056] The specific method for fabricating a 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor described in this invention is as follows.
[0057] S1. Fabrication of the SiO2 / p-Si substrate for the device: A 100 nm SiO2 layer was grown on the p-type Si layer using plasma-enhanced chemical vapor deposition (PECVD). The substrate was then ultrasonically cleaned sequentially with acetone, ethanol, and deionized water for 20 min to remove organic impurities. Finally, it was dried with nitrogen gas. The resulting structure is shown below. Figure 2 As shown.
[0058] S2. Fabrication of devices at both ends of β-Ga2O3 nanoribbons, the method comprising the following steps:
[0059] S21. Using 3M tape, 140 nm thick β-Ga2O3 nanoribbons were mechanically peeled from the (100) crystal plane of the β-Ga2O3 bulk single crystal and transferred to the SiO2 / p-Si substrate of step S1. The resulting structure is as follows. Figure 3 As shown.
[0060] S22. Fix the sample on the spin coater tray and spin-coat with electron beam photoresist. Spin coater speed: forward rotation 500 rad / min, forward rotation time 5s; backward rotation 4000 rad / min, backward rotation time 65s.
[0061] S23. Place the sample on a drying rack for softening. The drying rack temperature is 170℃, and the drying time is 3 minutes and 40 seconds. The resulting structure is as follows: Figure 4 As shown.
[0062] S24. Electron beam exposure is performed on the sample to symmetrically fabricate drain and source patterns at both ends of the β-Ga2O3 nanoribbon.
[0063] S25. Immerse the exposed sample in the developing solution for 65 seconds. Immediately remove the sample and dry it with N2. Then immerse the sample in isopropanol solution for 65 seconds for fixing. Immediately remove the sample and dry it with N2.
[0064] S26. Electron beam evaporation is used to deposit a multilayer metal Ti / Al / Au on the side of the sample with the photolithographic pattern, which is used as the source and drain electrodes of the device. The thickness of the multilayer metal is 15 / 90 / 80 nm, and the formation temperature is 50 °C.
[0065] S27. Immerse the sample in acetone solution and use an ultrasonic cleaner to remove and strip the remaining photoresist until the surface pattern of the sample is fully revealed. Then remove the sample, rinse it with deionized water, and dry it with N2 to obtain the devices at both ends of the β-Ga2O3 nanoribbon. Figure 5 and Figure 6 As shown.
[0066] S28. Annealing under nitrogen conditions using a rapid thermal annealing apparatus to achieve good ohmic contact of the electrodes, with an annealing temperature of 460℃ and an annealing time of 90s.
[0067] S3. Preparation of 1T'-MoTe2 / Ga2O3 Schottky barrier gate, the method comprising the following steps:
[0068] S31. Using a blue film, 30 nm thick few-layer 1T'-MoTe2 nanosheets were mechanically exfoliated from the 1T' phase MoTe2 bulk crystal and transferred onto a flat PDMS substrate, as shown. Figure 7 As shown. The PDMS is polydimethylsiloxane, a transparent, viscous polymer solid material in the prior art.
[0069] S32. With the assistance of a two-dimensional material transfer platform, the sample obtained in step S31 is aligned and transferred to the middle region of the β-Ga2O3 nanoribbon channel layer. The sample stage is heated to 70°C, and the resulting structure is as follows. Figure 8 As shown.
[0070] S33. Fix the sample obtained in step S32 onto the spin coater tray and spin coat it with electron beam photoresist. Spin coater speed: forward rotation 500 rad / min, forward rotation time 5s; backward rotation 4000 rad / min, backward rotation time 65s.
[0071] S34. Place the sample obtained in step S33 on the baking table for soft baking at a heating temperature of 90°C for 3 minutes.
[0072] S35. Electron beam exposure is performed on the sample obtained in step S34 to fabricate an electrode pattern at one end of the 1T'-MoTe2 nanosheet.
[0073] S36. Immerse the exposed sample in the developer for 65 seconds, then immediately remove the sample and dry it with N2. Next, immerse the sample in isopropanol for 65 seconds for fixing, then immediately remove the sample and dry it with N2.
[0074] S37. Electron beam evaporation is used to deposit a Ti / Au layer on the side of the sample with the photolithographic pattern. The thickness of the layer is 10 / 50 nm, and the formation temperature is 50 °C.
[0075] S38. Immerse the sample in acetone solution and heat it on a hot plate at 50°C for 1 hour. Then remove the sample and rinse it with deionized water until the surface pattern is fully visible. Dry it with N2 to obtain the desired result. Figure 1 and Figure 9 The final device shown.
[0076] The transfer characteristics of the device in this embodiment and the comparative device were measured using a semiconductor device analyzer at room temperature (27°C). The comparative example is a common β-Ga₂O₃ bottom-gate MOSFET. Figure 10 As can be seen from the comparison, the device in this embodiment has a significantly lower turn-on voltage, i.e., a lower threshold voltage V. th It operates at -5.7V, with a lower turn-off current of <100fA. Its switching current is greater than I... ON / I OFF Up to 1.6×10 8 The subthreshold swing SS is 120.7mV / dec.
[0077] The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor fabricated in this embodiment maintains good electrical performance and interface characteristics even at deep cryogenic temperatures, such as... Figure 11 As shown. At a low temperature of -100℃, its forward and reverse scan curves almost completely overlap, and the hysteresis is close to 0. Its switching current ratio I ON / I OFF 5×10 5 Threshold voltage V th With a voltage of -6.2V and a subthreshold swing (SS) of 383mV / dec, it can be applied to harsh cryogenic working environments.
[0078] The principle lies in the fact that the few-layer MoTe2 nanosheets of the 1T' phase are two-dimensional metallic materials. They are bonded to the wide-bandgap β-Ga2O3 channel via van der Waals forces, forming a stable van der Waals Schottky junction. This improves the gate control capability of the β-Ga2O3 transistor, achieving a very low turn-on voltage, very low turn-off current, a high on / off current ratio, and a steep subthreshold swing. Furthermore, the clean and atomically flat van der Waals interface has a very low interface trap density, which reduces the hysteresis of the transfer curve.
[0079] For those skilled in the art, various other corresponding changes and modifications can be made based on the technical solutions and concepts described above, and all such changes and modifications should fall within the protection scope of the claims of this invention.
Claims
1. A 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor, characterized in that, A β-Ga2O3 nanoribbon is disposed on a SiO2 / p-Si substrate, with the drain and source electrodes connected to its two sides respectively; a 1T'-MoTe2 nanosheet is disposed on the upper surface of the β-Ga2O3 nanoribbon, with one end of the 1T'-MoTe2 nanosheet connected to the β-Ga2O3 nanoribbon and the other end connected to the gate electrode.
2. The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor according to claim 1, characterized in that, One end of the 1T'-MoTe2 nanosheet is connected to the middle of the β-Ga2O3 nanoribbon.
3. The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor according to claim 1, characterized in that, The SiO2 / p-Si substrate comprises a SiO2 layer and a p-type Si layer stacked sequentially from top to bottom, and the β-Ga2O3 nanoribbon is disposed on the end face of the SiO2 layer away from the p-type Si layer.
4. The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor according to claim 3, characterized in that, The SiO2 thickness is 100 nm.
5. The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor according to claim 1, characterized in that, The 1T'-MoTe2 nanosheets are few-layer two-dimensional materials of the 1T' phase.
6. The 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor according to claim 1, characterized in that, The 1T'-MoTe2 nanosheets and β-Ga2O3 nanoribbons extend perpendicularly to the upper surface of the SiO2 / p-Si substrate.
7. The preparation method, characterized in that, The method for fabricating a 1T'-MoTe2 / Ga2O3 Schottky gate field-effect transistor as described in any one of claims 1 to 6 includes the following steps: S1. Preparation of SiO2 / p-Si substrate; S2. Preparation of β-Ga2O3 nanoribbons and electrodes at both ends; S3. Prepare 1T'-MoTe2 nanosheets to form a Schottky barrier gate.
8. The preparation method according to claim 7, characterized in that, Step S1 specifically involves: growing a 100 nm SiO2 layer on a p-type Si layer using plasma-enhanced chemical vapor deposition; sequentially ultrasonically cleaning the substrate surface for 20 min each with acetone, ethanol, and deionized water to remove organic impurities; and finally drying it with nitrogen gas.
9. The preparation method according to claim 8, characterized in that, Step S2 specifically includes the following sub-steps: S21. Using 3M tape, mechanically peel off a 140nm thick β-Ga2O3 nanoribbon from the (100) crystal plane of the β-Ga2O3 bulk single crystal and transfer it to the SiO2 / p-Si substrate of step S1. S22. Spin coat electron beam photoresist onto the spin coater tray; spin coater speed: forward spin 500 rad / min, forward spin time 5s; backward spin 4000 rad / min, backward spin time 65s; S23. Soften the glue on the drying table. The heating temperature of the drying table is 170℃, and the drying time is 3 minutes and 40 seconds. S24. Perform electron beam exposure to symmetrically fabricate drain and source patterns at both ends of the β-Ga2O3 nanoribbon; S25. Immerse in developer for 65 seconds, then remove and dry with N2; then immerse in isopropanol solution for 65 seconds, then remove and dry with N2. S26. Electron beam evaporation is used to deposit a multilayer metal Ti / Al / Au on the side with the photolithographic pattern, which are used as the source and drain of the device, respectively; the thickness of the multilayer metal is 15 / 90 / 80 nm, and the formation temperature is 50℃; S27. Soak in acetone solution, use an ultrasonic cleaner to remove the remaining photoresist until the surface pattern is fully visible, rinse with deionized water and dry with N2. S28. Annealing under nitrogen conditions using a rapid thermal annealing apparatus to obtain an ohmic contact electrode; annealing temperature 460℃, annealing time 90s.
10. The preparation method according to claim 9, characterized in that, Step S3 specifically includes the following sub-steps: S31. Using a blue film, a few-layer 1T'-MoTe2 nanosheet with a thickness of 30 nm was mechanically exfoliated from the 1T' phase MoTe2 bulk crystal and transferred onto a flat PDMS. S32. With the assistance of a two-dimensional material transfer platform, the sample obtained in step S31 is aligned and transferred to the middle region of the β-Ga2O3 nanoribbon, and the sample stage heating temperature is 70℃. S33. Fix the sample obtained in step S32 on the spin coater tray and spin coat electron beam photoresist. Spin coater speed: forward rotation 500 rad / min, forward rotation time 5s; backward rotation 4000 rad / min, backward rotation time 65s. S34. Soft bake on the baking table at a heating temperature of 90℃ for 3 minutes; S35. Perform electron beam exposure to create an electrode pattern at one end of the 1T'-MoTe2 nanosheet; S36. Immerse in developing solution for 65 seconds, then remove and dry with N2; then immerse in isopropanol for fixing for 65 seconds, then remove and dry with N2. S37. A multilayer metal Ti / Au is deposited on the side of the sample with a photolithographic pattern using an electron beam evaporation process to serve as the gate of the device: the thickness of the multilayer metal is 10 / 50 nm, and the formation temperature is 50 °C. S38. Immerse in acetone solution and place on a hot plate for heating. The hot plate temperature is 50°C and the heating time is 1 hour. After removing, rinse with deionized water until the surface pattern is fully visible. Blow dry with N2 to obtain the final device.
Citation Information
Patent Citations
Preparation method of grid enhanced gallium nitride field effect device with P type 2D material
CN108365008A
Preparation method of high-performance gallium oxide field effect transistor with insulating substrate
CN112133755A
